Inelastic Tunnel Transport and Nanoscale Junction Thermoelectricity with Varying Electrode Topology. Issue 6 (25th April 2021) - Roy, Talem Rebeda; J, John Donald Raj; Sen, Arijit
Abstract: Intricacies in the charge transport behavior of single‐molecule junctions often revolve around the complex nature of orbital hybridization stemming from diversified metal‐molecule coupling at interfaces. It will hence be pertinent to fathom the myriad aspect of inelastic charge transport and nanoscale thermoelectricity in single‐molecule junctions. It is examined from first‐principles, achiral and chiral quasi‐1D electrodes to understand the role of junction heterogeneity in overall thermoelectric behavior during charge transport. This calculated inelastic electron tunneling spectra exhibit intense peaks in the low‐frequency regime (< 25 meV) with characteristic bending and rocking modes, which auger well with the available measured data. It is subsequently found that the thermopower can be as high as 212 µV K −1 for σ‐saturated molecular moieties, depending strongly on the configuration of electrodes. Besides, a majority of such single‐molecule junctions turn out to deviate from the Wiedemann–Franz law, leading to anomalies in the electronic thermal conductance. The authors' analysis suggests that as nanoscale electrodes, Au(111) nanowires are likely to render a relatively high thermoelectric figure of merit ( ZT > 1) for a small molecular junction at room temperature. Discerning the diversity as driven exigently by the electrode topology may thus augment the device performance in terms of thermal stability at molecular scale. Abstract : Utilizing first‐principles quantum transport method, inelastic electron tunneling and device thermoelectricity at a molecular scale is simulated for a host of quasi‐1D gold electrodes of diverse topology. Au(111) NWs can potentially yield a high ZT upon interfacing with σ‐saturated or π‐conjugated molecular moieties. One may envisage green thermoelectricity at device level by engineering smart architectures based on electrode topology.